2012
DOI: 10.3168/jds.2011-4893
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal infusion of α-linolenic acid affects fatty acid metabolism in the mammary gland of lactating dairy cows

Abstract: Increasing the concentration of α-linolenic acid (LNA; 18:3 cis-9,cis-12,cis-15) in blood might affect fatty acid (FA) metabolism in the mammary gland of dairy cows. The objective was to determine the effects of different arterial concentrations of 18:3 cis-9,cis-12,cis-15 (18:3n-3) achieved via duodenal infusions with LNA on mammary uptake [assessed via arterial-rectificative venous concentration (AC-RVC) differences], synthesis of FA, and mammary gland FA balance in lactating dairy cows. Four primiparous lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Despite part of C16 : 0 and, to lesser extend to C14 : 0, can derived from circulating lipids, short and medium fatty acid can be used to evaluated the mammary de novo FA synthesis (Glasser et al 2005). In our trial, higher level of dietary C18 : 3 n -3 and subsequent higher mammary uptake of this FA could have induced an inhibition effect on FA synthesis in agreement with the findings of Yang et al (2012).…”
Section: Resultssupporting
confidence: 93%
“…Despite part of C16 : 0 and, to lesser extend to C14 : 0, can derived from circulating lipids, short and medium fatty acid can be used to evaluated the mammary de novo FA synthesis (Glasser et al 2005). In our trial, higher level of dietary C18 : 3 n -3 and subsequent higher mammary uptake of this FA could have induced an inhibition effect on FA synthesis in agreement with the findings of Yang et al (2012).…”
Section: Resultssupporting
confidence: 93%
“…Emery et al (1965) found no difference in the concentrations of glucose and acetate in arterial and venous coccygeal blood. This premise has been accepted in studies on mammary gland metabolism of AA (Lykos and Varga, 1997;Doepel and Lapierre, 2010) and fatty acids (Yang et al, 2012). Moorby et al (2002) reported that although concentrations of some AA were slightly different between coccygeal arterial and coccygeal venous blood, the differences were not significant.…”
Section: Mammary Metabolism Of Nitrogenous Compoundsmentioning
confidence: 84%
“…This result is in agreement with Zheng et al (2005), who reported that the concentration of C14:0 and C16:0 in milk fat was significantly lower in response to added vegetable oils. Moallem et al (2012) and Yang et al (2012) also showed a strong negative correlation between ALA, short-chain, and medium-chain fatty acids in cow milk fat when flaxseed oil and ALA were infused into the digestive tract. Similarly, Bu et al (2007) reported that the proportion of short-chain and medium-chain fatty acids (C10:0, C12:0, C14:0, and C16:0) was lower in milk from cows that were given soybean oil or flaxseed oil at 4% of the diet DM compared with CON group.…”
Section: Milk Fat Fatty Acid Compositionmentioning
confidence: 91%